The Role of Dreams of Ads and Exposure to Ads on Purchase Intention with The Moderation Effect of Price - Fara Hajar Puspita Putri; Tantri Yanuar Rahmat Syah (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2021)
This study examines dream of ads and exposure to ads on purchase intention, moderated by Price, and Dreams of Ads as mediating variables. This study aims to explore the relationship between these variables to provide additional information in marketing science and to provide information in the field of marketing in creating managerial strategies for companies. The respondents of this research are individuals who have dreamed of their dream products in Indonesia. The analysis test of this research used the method of the Structural Equation Model (SEM). The total sample in this study was 180 respondents. This study shows a positive influence between Exposure to Ads on Dreams of Ads, Dream of Ads on Purchase Intentions, Exposure to Ads on Purchase Intentions, and the moderating role of Price. However, the mediating part of Dreams of Ads between Exposure to Ads and Purchase Intention does not have a significant relationship. The implication of this research is to provide managerial advice to companies in making advertisements that follow the dreams of the company's target market.